2016
DOI: 10.1210/jc.2016-2786
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Subjects Differentially Respond to Dietary Capsaicin Correlating with Specific Gut Enterotypes

Abstract: Our study showed that gut enterotypes may influence the beneficial effects of dietary CAP, providing new evidence for the personalized nutrition guidance of CAP intervention on health promotion linking with gut microbiota patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
97
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 40 publications
13
97
2
4
Order By: Relevance
“…Interestingly, our recent study has shown similar results with CAP intervention in human subjects (16). This would indicate the possibility that lower abundance of Gram-negative microbiota must be responsible for the low abundance of KEGG orthology (KO) belonging to the LPS biosynthesis pathway in the HFD+C group.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Interestingly, our recent study has shown similar results with CAP intervention in human subjects (16). This would indicate the possibility that lower abundance of Gram-negative microbiota must be responsible for the low abundance of KEGG orthology (KO) belonging to the LPS biosynthesis pathway in the HFD+C group.…”
Section: Discussionsupporting
confidence: 74%
“…2D and E and G and H). Interestingly, our previous study also found that the levels of butyrogenic bacteria are elevated in humans after 2 weeks of CAP intervention (16). Bacterial butyrate production is a key function attributed to a “healthy” gut microbiota because of the preferred use of this SCFA as an energy source for intestinal epithelial cells (29).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…SCFAs were measured by gas chromatography from caecum contents as described previously [40]. A 1:5 dilution of caecum in 1 M HCl was centrifuged (12000 × g , 15 min), and diethylacetic acid (Sigma) was added to a final concentration of 1 mM as an internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…Using these enterotypes, microbiome-based nutritional or drug metabolism can be estimated and clinically useful to prevent idiosyncratic hypersensitivity to food and drugs, and metabolic activation-induced toxicity [3]. Moreover, nutritional recommendation could be individually selected based on personal enterotypes to control the metabolism-linked disorders such as hypercholesterolemia, diabetes and obesity [4]. …”
Section: Features Of Stability Diversity Functional Redundancy Andmentioning
confidence: 99%